2005
DOI: 10.1093/nar/gki165
|View full text |Cite
|
Sign up to set email alerts
|

Processing of a complex multiply damaged DNA site by human cell extracts and purified repair proteins

Abstract: Clustered DNA lesions, possibly induced by ionizing radiation, constitute a trial for repair processes. Indeed, recent studies suggest that repair of such lesions may be compromised, potentially leading to the formation of lethal double-strand breaks (DSBs). A complex multiply damaged site (MDS) composed of 8-oxoguanine and 8-oxoadenine on one strand, 5-hydroxyuracil, 5-formyluracil and a 1 nt gap on the other strand, within 17 bp was built and used to challenge several steps of base excision repair (BER) path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 44 publications
3
89
0
Order By: Relevance
“…They are likely to consist of closely spaced SSBs together with oxidative base damages and/or complex DSBs. Several model studies suggested that some combinations of lesions may be lethal and even mutagenic (David-Cordonnier et al 2000Harrison and Malyarchuk 2002;Harrison et al 1999;Eot-Houllier et al 2005;Budworth et al 2005). At the cellular level, LMDS were thought to be detectable, after conversion into DSBs by specific DNA glycosylases (Fpg) and/or endonucleases (Nth, Nfo) through selective cuts at oxidatively damaged sites in opposite DNA strands, using conventional pulsed-field gel electrophoresis (Sutherland et al 2000).…”
Section: Importance Of Radiolesions Induced At Low Dosesmentioning
confidence: 99%
“…They are likely to consist of closely spaced SSBs together with oxidative base damages and/or complex DSBs. Several model studies suggested that some combinations of lesions may be lethal and even mutagenic (David-Cordonnier et al 2000Harrison and Malyarchuk 2002;Harrison et al 1999;Eot-Houllier et al 2005;Budworth et al 2005). At the cellular level, LMDS were thought to be detectable, after conversion into DSBs by specific DNA glycosylases (Fpg) and/or endonucleases (Nth, Nfo) through selective cuts at oxidatively damaged sites in opposite DNA strands, using conventional pulsed-field gel electrophoresis (Sutherland et al 2000).…”
Section: Importance Of Radiolesions Induced At Low Dosesmentioning
confidence: 99%
“…Experimental studies suggest much slower rejoining kinetics for DSBs induced by high-LET radiations compared with low-LET radiations (25,26) reflecting the increased complexity of DSBs induced by high-LET radiation (27). Studies with synthetic oligonucleotides containing specific types of clusters suggest that clustered DNA lesions are resistant to processing by glycosylases or endonucleases (28)(29)(30)(31)(32)(33). In vivo studies have shown that the number of abasic clusters formed in human monocytes after irradiation did not return to background levels for over 14 days (14).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of damage in LMDS has been shown to be less efficient than that of single lesions (17)(18)(19). Moreover, as a consequence of their repair, LMDS can induce highly genotoxic double-strand breaks (20,21). In the case of tandem lesions that could be considered as a class of LMDS in which the two modifications are adjacent to each other and located on the same strand, the presence of thymidine glycols (ThdGly) neighboring 8-oxodGuo has been shown to modulate the efficacy of excision of the oxidized purine by its specific human glycosylase hOGG1 (22).…”
mentioning
confidence: 99%